Ekonomi Kerakyatan : Sekedar Jargon Politik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT This paper examines the communal economy development in Indonesia by reviewing several related literatures developed by George and Shorey (1978), Wijaya (1987), Ranuwihardjo (1999), and Baswir (1999). This issue emanates since an ambiguous and pessimistic question still remains regarding what, why, how, what purpose, and for whom the communal economy is aimed to